The Ku Klux Klan in the Southwest - Alexander, Charles C. (Book collections on Project MUSE., 2015)
This is a study of a disturbing phenomenon in American society -- the Ku Klux Klan -- and that eruption of nativism, racism and moral authoritarianism during the 1920s in the four states of the Southwest -- Texas, Louisiana, Oklahoma, and Arkansas -- in which the Klan became especially powerful. The hooded order is viewed here as a move by frustrated Americans, through anonymous acts of terror and violence, and later through politics), to halt a changing social order and restore familiar orthodox traditions of morality. Entering the Southwest during the post-World War I period of discontent an.